The Russian factor in Ukrainian identity - Sinisha Kuko (Політичні дослідження, 2023)
In the eighteenth century, the former Mongol vassal Moscow usurped the name and heritage of the early medieval Kyivan state. Starting with these eighteenth-century events, Russia became a special type of civilisation ― neither European nor Asian, but a permanently autocratic regime, and subsequently a major obstacle to the maturation of Ukraine's pre-modern ethnic and modern national identity. Today, Russia's imperial identity influences Ukraine as an undisguised old-fashioned, peculiar empire, and for Ukraine it is a key factor in international relations. Russia's demonstration of anti-democratic sentiments against the „totalitarian West" is evidenced by its outright denial of Ukrainian identity when Ukraine tries to turn to the West. Putin's extremely aggressive, dismissive attitude and humiliation of the Ukrainian national idea of separation from Russia have strengthened and intensified Kyiv's desire to leave Moscow's fatal orbit. During the current bloody struggle for existence, historical time is accelerating and an anti-Russian and pro-European national identity is being formed in Ukraine. At the same time, the war for Ukraine is bringing together the pre-war divided identities of Ukrainians, who have rallied around the idea of a common Ukrainian pro-European destiny against an aggressive and brutal Russia. On the other hand, Russia's invasion of Ukraine accelerated the transition of the Russian political regime to dictatorial rule and certain pro-fascist methods, including but not limited to the elimination of any public opposition or dissident opinion. Within the framework of the sociology of history and constructivist theory of international relations, Russia is analysed as a decisive factor in international relations for Ukraine and an independent variable of causality with the existence of Ukraine.